Respons Tanaman Padi Pada Media Tanam Tanpa-Tanah Berbasis Irigasi Berselang - Tirto Wahyu Widodo; Damanhuri Damanhuri; Ilham Muhklisin; Sonia Budiarti; Dian Agustina (Institut Pertanian Bogor, 2024)
Rice cultivation without land as an urban farming method is carried out to produce food in a subsistence manner. This experiment aimed to examine the response of rice plants to non-soil planting media based on alternate wetting-drying irrigation. This work was conducted at the screen house in Sumberjeruk Village, Jember Regency (8°07'42.9